A study of repetition in English and Vietnamese folk songs - Hồ, Đoàn Như Thương; Phan Văn Hòa, Assoc.Prof.Dr. (Đà Nẵng : The University of Da Nang, 2015)
Introduction; Literature review and theoretical background; Research design and methodology; ...
includes appendix and references.
Master thesis in social sciences and humanities. Field: The English language.Code: 60.22.02.01.
Keywords: The English language; repetition in English -- Vietnamese folk songs